G-Quadruplex Identification in the Genome of Protozoan Parasites Points to Naphthalene Diimide Ligands as New Antiparasitic Agents - Belmonte-Reche, Efres; Martínez-García, Marta; Guédin, Aurore; Zuffo, Michela; Arévalo-Ruiz, Matilde; Doria, Filippo; Campos-Salinas, Jenny; Maynadier, Marjorie; López-Rubio, José Juan; Freccero, Mauro; Mergny, Jean-Louis; Pérez-Victoria, José María; et al. (Journal of medicinal chemistry, 2018)
G-quadruplexes (G4) are DNA secondary structures that take part in the regulation of gene expression. Putative G4 forming sequences (PQS) have been reported in mammals, yeast, bacteria, and viruses. Here, we present PQS searches on the genomes of T. brucei, L. major, and P. falciparum. We found telomeric sequences and new PQS motifs. Biophysical experiments showed that EBR1, a 29 nucleotide long highly repeated PQS in T. brucei, forms a stable G4 structure. G4 ligands based on carbohydrate conjugated naphthalene diimides (carb-NDIs) that bind G4's including hTel could bind EBR1 with selectivity versus dsDNA. These ligands showed important antiparasitic activity. IC50 values were in the nanomolar range against T. brucei with high selectivity against MRC-5 human cells. Confocal microscopy confirmed these ligands localize in the nucleus and kinetoplast of T. brucei suggesting they can reach their potential G4 targets. Cytotoxicity and zebrafish toxicity studies revealed sugar conjugation reduces intrinsic toxicity of NDIs.
Keywords: Animals; Humans; Naphthalenes; buněčné linie; Zebrafish; lidé; zvířata; naftaleny; Ligands; ligandy; G-Quadruplexes; Imides; Genome, Protozoan; Telomere; G-kvadruplexy; Antiparasitic Agents; Cell Line; dánio pruhované; telomery; genom protozoální; antiparazitární látky; imidy